The Affective Scope: Entering China's Urban Moral and Economic World Through Its Emotional Disturbances - Pettier, Jean Baptiste (Anthropology of Consciousness, 2016)
From an outsider's perspective, today's Popular China might appear as a self-confident and triumphant country. However, a large-scale examination of the country's recent moral controversies reveals a very different picture, one that has much to do with the widespread local public perception of an ongoing "moral crisis" (Kleinman et al., 2011), whose examination requires careful attention placed on the ethical and affective aspects of the everyday lives of today's Chinese people. In this article, I propose to examine the anguish that Chinese bachelor youths and their concerned parents undergo and express, as they are confronted with the difficult process of finding a suitable mate for marriage. I examine the fears their celibacy generates, the mutual distrust that participants taking part in bachelors' parents gatherings demonstrate, and the disputes these encounters engage. I analyze the moral world of today's urban China from the perspective of the very feelings and affects that pervade it. Highlighting the ways in which my interlocutors shared their emotions with me along the course of my fieldwork, carried out in the cities of Beijing and Chengdu, I will insist on the importance of these affects within an anthropological approach. The moral sensitivities contained in the maintenance of the economic and social situations of one's family reveal themselves as an exceptional resource for knowledge. By examining the political economy of sentiments within which parents and their children find themselves entrapped, I argue that we can gain a deeper understanding of the concrete consequences of today's societal transformations.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Affect; China; Methodology; Moral; Sentiments